The effect of air quality due to household waste sewers on the growth of cayenne pepper (Capsicum frustescens L.) - Suhendra Iskandar (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
Research has been carried out on the effect of air pollution due to household sewage on the growth of cayenne pepper (Capsicum frustescens L.). A total of 12 samples were divided into 4 groups: 3 samples in the group placing planting locations near the sewers, 3 samples in the group placing planting locations near the sewers and giving liquid NPK fertilizer once a day, 3 samples in the group placing planting locations in places with high-quality clean air, and 3 samples in the planting location group in places with clean air quality and application of liquid NPK fertilizer once a day. The sample growth was observed for 90 days to see the difference in growth in each sample group. It was found that the samples in the group placing the planting location near the sewer, both those who were given and those who were not given liquid NPK fertilizer once a day, showed severe shrinkage symptoms in 13-14 days after planting. The samples placed in a place with clean air quality without liquid NPK fertilizer showed growth disorders in the 60 days after planting. Meanwhile, samples placed in a place with clean air quality and given liquid NPK fertilizer once a day showed fertile growth.